Liver transplantation as a potentially lifesaving measure in neuroblastoma stage 4S. (2nd January 2017) - Holsten, Till; Schuster, Tobias; Grabhorn, Enke; Hero, Barbara; Frühwald, Michael C.
ABSTRACT: Neuroblastoma (NBL) stage 4s is an incompletely understood phenomenon with variable clinical course. While the majority of patients may undergo spontaneous regression and achieve complete resolution without intensive therapy, a small proportion is at increased risk of developing secondary complications. One such situation is liver insufficiency due to diffuse metastases. We report a patient suffering from NBL 4S who required double lifesaving liver transplantation. Abdominal and respiratory complications due to hepatomegaly are crucial determinants for treatment intensity and duration in 4S NBL[1, 2] . We provide an algorithm in order to facilitate the clinical decision when dealing with similar potentially life-threatening events.